Mycoplasma bovis Invades Non-Phagocytic Cells by Clathrin-Dependent Endocytic Pathways and Escapes from Phagocytic Vesicles - Bin Li; Yabin Lu; Yaru Feng; Xiaolong Jiao; Qiuyu Zhang; Mengting Zhou; Yuyu Zhang; Jian Xu; Yuefeng Chu; Duoliang Ran (Pathogens)
Mycoplasma bovis (M. bovis) is capable of causing pneumonia, arthritis, mastitis, and various other ailments in cattle of all age groups, posing a significant threat to the healthy progression of the worldwide cattle industry. The invasion of non-phagocytic host cells serves as a pivotal mechanism enabling M. bovis to evade the immune system and penetrate mucosal barriers, thereby promoting its spread. To investigate the differences in M. bovis invasion into four types of non-phagocytic cells (Madin–Darby bovine kidney (MDBK) cells, embryonic bovine lung (EBL) cells, bovine embryo tracheal (EBTr) cells and bovine turbinate (BT) cells) and further elucidate its invasion mechanism, this study first optimized the experimental methods for M. bovis invasion into cells. Utilizing laser scanning confocal microscopy, transmission electron microscopy, and high-content live-cell imaging systems, the invasion process of M. bovis into four types of non-phagocytic cells was observed. The invasion rates of three different strains of M. bovis (PG45, 07801, 08M) were quantified through the plate counting method. In order to clarify the specific pathway of M. bovis invasion into cells, chlorpromazine (CPZ), amiloride (AMI), and methyl-β-cyclodextrin (M-β-CD) were used to inhibit CLR-mediated clathrin-dependent endocytosis (CDE) pathway, macropinocytosis, and lipid raft pathway, respectively. Subsequently, the invasion rates of PG45 into these four types of cells were measured. Using siRNA technology, the expression of clathrin (CLR) in EBL cells was knocked down to further verify the role of CLR in the invasion process of M. bovis. The results showed that the optimal conditions for M. bovis to invade non-phagocytic cells were a multiplicity of infection (MOI) of 1000 and an optimal invasion time of 4 h. All three strains of M. bovis have the ability to invade the four types of non-phagocytic cells, yet their invasion abilities vary significantly. Observations from transmission electron microscopy further confirmed that at 120 min post-infection, PG45 had successfully invaded EBL cells and was present within endocytic vesicles. It is noteworthy that almost all PG45 successfully escaped from the endocytic vesicles after 240 min of infection had passed. Through chemical inhibition experiments and CLR protein knockdown experiments, it was found that when the CDE and lipid raft pathways were blocked or CLR protein expression was reduced, the invasion rates of PG45, 07801, and 08M in MDBK, EBL, EBTr, and BT cells were significantly decreased (p < 0.05). The above results indicate that M. bovis can invade all types of non-phagocytic cells through endocytic pathways involving CDE (clathrin-dependent endocytosis) or lipid raft-mediated endocytosis, and possesses the ability to escape from phagosomes.